New record of Haplometroides intercaecalis (Digenea, Plagiorchiidae) infecting a Brazilian snake - Silva, R. J. [UNESP]; Beda, A. F.; Ferreira, V. L. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
Phalotris matogrossensis (Serpentes, Colubridae) was reported as a new host for Haplometroides intercaecalis ( Digenea, Plagiorchiidae). The host snake was obtained from the municipality of Anastacio, state of Mato Grosso do Sul, Brazil. One specimen of H. intercaecalis was recovered from the esophagus of the host and identified by the intercecal position of the vitellaria in the pre-acetabular region. This paper describes the second report of the occurrence of this trematode in fossorial snakes of the genus Phalotris in the state of Mato Grosso do Sul, Brazil.
Keywords: Digenea; haplometroides intercaecalis; plagiorchiidae; phalotris matogrossensis; Colubridae; new host